Use of mobile high-resolution device for remote frozen section evaluation of whole slide images - Joel Ramey; Kar Ming Fung; Lewis A Hassell (Elsevier, 2011)
Introduction: With recent advances, it is now possible to view whole slide images (WSI) on mobile, high-resolution, viewing devices (MVD). This creates a new paradigm in which MVDs may be used for consultation and/or diagnosis. Validation of the results with devices is important for practitioners and regulators. We evaluated the use of MVDs in frozen section (FS) interpretation. Methods: A series of 72 consecutive FS cases were selected for potential inclusion in the study. A 67 case subset of these were successfully scanned at 20x magnification. Scan times were recorded. A sample of WSI FS cases, with gross and clinical information, was presented to six pathologists on an iPad MVD using the Interpath application. Times to diagnosis were recorded. Results were compared with the original reported and final diagnosis. Participants also completed a survey assessing image quality, interface, and diagnostic comfort level. Results: Scan times averaged two minutes and 46 seconds per slide, (standard deviation [SD] 2 minutes 46 seconds). Evaluation times averaged 4 minutes and 59 seconds per case, range to 13 minutes and 50 seconds, SD 3 minutes 48 seconds. Concordance between initial FS diagnosis and rendered through the MVD was 89%. Minor discrepancies made up 8% and major disagreements 3%. The kappa statistic for this series is 0.85. Participants rated the experience at 5 on a 10-point scale, range 3 to 7. Two-thirds found the image quality to be adequate, half were satisfied with image resolution, and 33% would be willing to make a diagnosis on the iPad, plus one only for special cases. Five of six respondents (83%) found the navigation with the study software difficult. Conclusion: Image fidelity and resolution makes the iPad potentially suitable for WSI evaluation of FS. Acceptable accuracy is attainable for FS interpretation. But, although possible to obtain acceptable results, use of the iPad with Interpath to view WSI is not easy and meets user resistance. The obstacle of slide navigation at high magnification could introduce frustrations, delays, or errors.